PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 7 PEMATANG PUDU KECAMATAN MANDAU - Kasuma Boti; lazim N lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Because low resulf of social study class IV SD Negeri 7 Pematang Pudu Kecamatan Mandau. From 30 students who achieve KKM just 11 students (36,66%) while students who did’nt complete 19 students (63,34%) with an average of 66,33.So the research try to chance learning models with apply models learning models Kooperatif Tipe Think Pair Share (TPS). The results obtained by the average value of 66,33 basic score increased in the first cycle of 16,83% to 83,16. In the second cycle the average value of students also increased by 18,17% to 84,50. On the basis of completeness score IPS students learning outcomes is only 36,66% (not finished). After the professor of applied learning model Think Pair Share (TPS) in the firs cycle classical completeness increased to 86,67% (finished), The second cycle of classical completeness obtained are increased to increase to 93,33%. Activiies of teachers at the first meeting of 70,83% with both categories. The second meeting increased to 75% in both categories. In the second cycle increased to 91,66% with the category very well. At a meeting of the second meeting of the second cycle, The activities of teachers increased to 95,83% with the category very well. Activities of studens in the first cycle of the first meeting activity students acquire a persentesa of 66,66% in both categories. The second meeting of the first cycle to 75% in both categories. At the first meeting of the second cycle of students activity increased to 87,5% with the category very well, And at the second meeting of the second cycle increased again to 95,83% with the category very well.Key Words: Kooperatif, TPS, IPS